The Effectiveness of Technique Group Guidance Services Homeroom To Increase Student Empathy - Lilis Suryani; Azam Arifyadi; Mardi Lestari; Dian Fitriani (FKIP - Universitas Riau, 2026)
Empathy is one of the important aspects of children's social and emotional development, especially in adolescence. Various problems arise due to low empathy at SMK Negeri 8 Palu which often causes anxiety which becomes a serious nuisance, especially among teenagers. The purpose of this study is to test the effectiveness of homeroom technique group guidance services in increasing student empathy. As an effort to create a comfortable learning environment at school. This study uses an experimental quantitative method using a pretest and posttest control group design, where there are tests before and after treatment. The subjects of this study were 13 students who were divided into 2 groups, namely the experimental and control groups. The results of this study showed that before the implementation of group guidance, the empathy level of the students of the experimental group (using homeroom techniques) obtained an average score of 49.5 and the students of the control group (without special techniques) obtained an average score of 48.5 which was in the medium category. After group guidance, the students of the experimental group increased with an average of 66.8 in the high category and the control group students increased to 63.8 in the high category. Based on the Mann Whitney test on the posttest in the experimental group and the control group, a significance value of 0.03 was obtained, the value <0.05 which means that it can be concluded that homeroom technique group guidance services are effective in increasing student empathy.